Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00394-015-1142-4
|View full text |Cite
|
Sign up to set email alerts
|

7-Keto-cholesterol and 25-hydroxy-1 cholesterol rapidly enhance ROS production in human neutrophils

Abstract: The present paper describes for the first time that two oxysterols (7-k-chol and 25-OH-chol) enhance the ROS production within a short period of time in human neutrophils, stimulate the translocation of the cytosolic components of NADPH oxidase to the cellular membrane and increase lysozyme secretion. These data suggest that both oxysterols are able to activate pro-inflammatory effects in human neutrophils which contrasts with the role assigned to the oxysterols when they act through LXR at long time of incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, excessive ROS accumulation can damage cellular proteins, lipids and DNA, leading to cell dysfunction, senescence and even cell death 4951 . Gonzalo Alba et al reported that excessive cholesterol enhanced ROS production in human neutrophils 52 . In the hyperlipidemia/hyperlipedimia mice/rats models, it was found that long-term high-fat diets led to the activation/elevation of NADPH Oxidase Catalytic Subunit-Like 3 (NOX3), uncoupling protein 2 (UCP2) and uncoupling protein 3 (UCP3), causing mitochondrial damage and apoptosis in inner ear 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive ROS accumulation can damage cellular proteins, lipids and DNA, leading to cell dysfunction, senescence and even cell death 4951 . Gonzalo Alba et al reported that excessive cholesterol enhanced ROS production in human neutrophils 52 . In the hyperlipidemia/hyperlipedimia mice/rats models, it was found that long-term high-fat diets led to the activation/elevation of NADPH Oxidase Catalytic Subunit-Like 3 (NOX3), uncoupling protein 2 (UCP2) and uncoupling protein 3 (UCP3), causing mitochondrial damage and apoptosis in inner ear 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Autoxidised cholesterols, including 7-KC and 7β-OHC have been shown to affect the bioavailability of other reactive oxygen and nitrogen species, by chemical interaction with nitric oxide. In addition, oxysterols easily diffuse into membranes where they affect receptor and enzyme function [34] ; furthermore, 7-KC promotes translocation of cytosolic NADPH oxidase components to the membrane in neutrophils and enhances rapid reactive oxygen species production [35] are well-known activators of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…7-oxysterols induce the induction and nuclear translocation of p53 in M1-t-p53 cells, enhancing LMP, mitochondrial translocation of Bax, mitochondrial membrane permeabilization, and the cytosolic release of cytochrome c, and cell death [31]. 7KCh has been shown to increase ROS levels in human neurocytes [32] rapidly. In addition, miRNA-1 was found to regulate the LXRα-ROS-mitochondrial pathway to regulate cardiomyocyte apoptosis [33].…”
Section: Discussionmentioning
confidence: 99%